The Effect Of Digital Content Creativity, Innovation Climate, And Curriculum Flexibility On Pedagogical Innovation: Penelitian - Antoni, Rivi; Supriyanto, Asep (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The research aims at making the role of digital content creativity, innovation environment, and flexible curriculum as the main factors of innovation in teaching to be recognized. The authors indicate that educational institutions are going through a tech-driven quality learning upgrade, which implies that these things have to be used in the most demanded and at the right time. Therefore, the study designed a quantitative-explanatory approach with 150 educators as respondents selected through the purposive sampling technique. Data was collected through a five-point Likert scale questionnaire and multiple linear regression was used for data analysis. The researchers revealed that besides the three independent variables, other factors also have a good and significant influence on teaching innovation. From a theoretical viewpoint, the research enriches the existing educational innovation literature by bringing together factors of digital creativity, organizational innovation climate, and curriculum flexibility. The findings of the study thus have guided educational institutions on how to increase their pedagogical innovation measures more effectively by relying on digital content creativity, building an innovation culture, and having a flexible curriculum.